ANALISA YURIDIS PERJANJIAN KERJA SAMA DEVELOPER DENGAN BANK TERHADAP KREDIT KEPEMILIKAN RUMAH SEJAHTERA FASILITAS LIKUIDITAS PEMBIAYAAN PERUMAHAN (PENELITIAN DI BANK ARTHA GRAHA INTERNASIONAL TBK CABANG MEDAN) - ROOSLITA ROOSLITA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Hasim Purba2. Sunarmi3. Suhaidi One of the problems studied in this research is related to the subsidized KPR or what is called KPR Rumah Sejahtera. It also focuses on the private relationship between bank and developer in which the developer of KPR Rumah Sejahtera acts as the seller and bank acts as the executor. The results of the research demonstrate that the target group of non subsidized KPR is people with middle-upper economy and that of subsidized KPR is people with middle-low economy. The down payment for KPR which is not subsidized by the government is 15% whereas that of subsidized KPR is IDR. 4,000,000.- (four million Rupiahs). In addition, the cooperation between Bank Artha Graha Internasional Tbk, Medan Branch and the developer is written in a cooperation agreement regulating the procedures, credit agreement and money disbursement which is made gradually, namely 80% before the signming of AJB, SKMHT, APHT and 20% after the signing of AJB, SKMHT, and APHT.Keywords: bank, developer, cooperation agreement.